The impact of religiosity on the psychological well-being of LGBT Christians. Issue 4 (2nd October 2019) - Boppana, Shilpa; Gross, Alan M.
Abstract: Individuals who identified as LGBT and Christian were administered measures of religiosity, their religious organization's view of homosexuality, internalized homonegativity (IH), and psychological well-being, including eudaimonic well-being (an approach to well-being that focuses on meaning, self-realization, and optimal functioning rather than pleasure attainment and pain avoidance), depression, stress, and anxiety. Religiosity was associated with higher levels of eudaimonic well-being and lower levels of depression, anxiety, and stress. Compared to participants who rated their church as rejecting of homosexuality, participants who rated their church as accepting of homosexuality had lower levels of depression and IH and higher levels of eudaimonic well-being. Moderation analyses indicated that church attendance moderated the relationship between religiosity and psychological well-being at moderate to high levels of church attendance, suggesting that church attendance plays a more important role than other religious practices in the relationship between religiosity and psychological well-being. Analyses indicated that IH and attendance did not mediate, nor did church type moderate, the relationship between religiosity and psychological well-being. Implications of findings are discussed.